Torkildsen's sport and leisure management - Wilson, Robert 1980-; Platts, Chris; Plumley, Daniel (Routledge, 2023)
"For nearly forty years Torkildsen's Sport and Leisure Management has been the most comprehensive and engaging introduction to sport and leisure management available to students at all levels. Now in its seventh edition, it is still the only textbook that covers all the key topics taught within contemporary sport and leisure management courses. This new edition includes expanded coverage of the practical managerial skills that students must develop if aiming for a career in the sport and leisure industry, from planning and managing people to marketing, entrepreneurship and the law. It includes four completely new chapters, on the global sport and leisure economy, historical development, cross sector collaboration, and management consultancy, reflecting important developments in contemporary sport and leisure. This edition retains the hallmark strengths of previous editions, including in-depth discussion of the social and cultural context of sport and leisure, full analysis of the public, private and voluntary sectors, and a review of key products and services. Richly illustrated throughout with up-to-date evidence, data, case-studies and international examples, each chapter also contains a range of useful pedagogical features, such as discussion questions, practical tasks and structured guides to further reading and resources. This is an important resource for students working in fields such as Sport Management, Sport Business, Sport Development, Leisure Management and Events Management. Dedicated online resources offer additional teaching and learning material for students and lecturers"--